Measurement of power supply for power quality analysis / Mohd Nazri Ismaili Mohamad - Mohamad, Mohd Nazri Ismaili (1998)
This study took approximately 36 weeks and two places are chosen for measurement of voltages, Main Switch Boards in Institute Technology Mara, Shah Alam. The objective of this study is to detemine and analize the quality of Power Supply for the data obtained.